ANovelty Methods of Cryptography Algorithms Into Layered Cipher Encryption and Decryption - Antoni, A; Aryza, Solly; Rizki Lubis, Azmi; Harahap, Bonar; Arfah, Mahrani (International Journal of Engineering and Technology, 2018)
Encryption is one method used to protect or maintain the data. Data that has encrypted will be kept confidential where the contents of the data are altered, so it does not correspond to the actual data. To be able to read data that has been encrypted earlier required a process called decryption. In the science of cryptography, the data will be safeguarded consists of three main components, that is the message that will be read (plaintext), the keys to perform cryptographic techniques (Key), and a random signal that is unreadable (ciphertext). Testing is done by sending the data in the form of words or sentences by using a secret key. Results of analysis of data from tests per-formed show that with the incorporation of some algorithm plated confidentiality of information can be safer because it takes several different stages to solve.